(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2020)
This study deals with the estimation of the economic impacts provided by the Belo Horizonte Municipal Tourism Company (Belotur) disbursements in 2018. It also aims to understand how the event intervened in order to understand the contributions under the lens of expanding revenue, generating employment and income from the disbursements made by Belotur. The method used was the Input-Output Matrix. For the matrix construction, it was necessary to analyze the published extracts related to Belotur expenses with the carnival and to carry out a classification of the disbursements of Belotur according to the National Classification of Economic Activities - CNAE. After these procedures, it was possible to estimate the impacts of carnival, which resulted from Belotur’s disbursements, have shown very positive results in the economy, significantly increasing the values of Minas Gerais’ production, value added, work earnings of the local population and also provided the creation of jobs.